Investigation of a high-sensitivity surface plasmon resonance sensor based on the eccentric core quasi D-shape photonic quasi-crystal fiber. Issue 11 (25th June 2021) - Sun, Yudan; Mu, Haiwei; Sun, Jiudi; Liu, Qiang; Liu, Chao; Liu, Wei; Zhao, Jin; Lv, Jingwei; Sun, Tao; Chu, Paul K.
Abstract : A highly sensitive refractive index (RI) sensor based on the surface plasmon resonance (SPR) phenomenon is proposed and demonstrated. The sensor is composed of a quasi D-shape ten-fold photonic quasi-crystal fiber (PQF) and indium tin oxide (ITO) film. The quasi D-shape and eccentric core structure strengthen coupling between the core mode and surface plasmon polariton (SPP) mode to enhance the sensing sensitivity, while the mechanical strength of the PQF is preserved. The properties of the sensor are determined numerically and optimized by the finite element method. In the RI range of 1.40–1.44, the maximum wavelength sensitivity and average wavelength sensitivity are 62, 000 nm/RIU and 26, 500 nm/RIU, respectively. Meanwhile, the loss spectra show smaller full-width at half-maximum and maximum FOM of 542.5 RIU −1 . This novel sensor which boasts ultra-high-sensitivity and excellent FOM has large potential in the determination of liquid RIs.